Bibliometric analysis of pedagogy of death - Ramos-Pla, Anabel; del Arco, Isabel; Mercadé-Melé, Pere (Frontiers in Education, 2025)
IntroductionThe objective of the present study is to identify the main emerging trends and research lines with respect to pedagogy of death.MethodsThe methodology was based on a bibliometric analysis of the main international scientific contributions found in the Web of Science (WoS) database. A total of 276 articles published between 2010 and 2023 were revised. The data were analyzed with VosViewer and Bibliometrix R which are software tools for building and visualizing bibliometric networks.ResultsThe main results show that the publications on pedagogy of death have increased through time, but decreased starting in 2020, both in the number of articles and citations.DiscussionScientific evidence is also presented on the need to continue working on pedagogy of death. This study contributes toward maximizing the visibility of pedagogy of death work in different contexts.